Profil Pasien Trauma Maksilofasial di Rumah Sakit Umum Daerah Waikabubak Sumba Barat Tahun 2018–2021: Hasil Penelitian - Djunaedi, Angela; Karjosukarso, Adityas Sukmadi (PT Kalbe Farma Tbk., 2024)
Introduction: Maxillofacial trauma is related to head trauma, mostly caused by motorcycle traffic accidents in Sumba. The limitations in diagnostic evaluation at rural hospitals present unique challenges to healthcare providers. This research describes some characteristics of maxillofacial trauma cases in Waikabubak General Hospital, West Sumba, East Nusa Tenggara. Methods: A retrospective descriptive study based on medical records between 2018 – 2021. Results: A total of 37 patients were included; the majority were in the 16 to 64 year-old age group (78%), with males (81%). Motorcycle road traffic accidents (73%) were the main cause, and the most common fracture site was the mandibula (35%). Skull AP lateral plain radiography was the most commonly used x-ray technique (49%). Cases were mostly discharged against medical advice (54%). Conclusion: Motorcycle road traffic accidents were the main cause of maxillofacial injuries, and the mandibula was the most common site of fractures.